Persepsi Siswa Kelas XI F.8 terhadap Pembelajaran Seni Budaya (Musik) di SMA N 1 Kecamatan Suliki - Hanif, Addinul; Kadir, Tulus Handra (YASIN, 2024)
This study aims to determine and describe the perceptions of students of class XI F.8 towards learning cultural arts (music) at SMAN 1 Suliki District. This research is descriptive in nature using a quantitative approach. The method used in this research is survey method. The object of this research is the students of class XI.F 8 SMA N 1 Suliki, which was chosen to explain the perception of students on the learning of cultural arts (music). The research data collection was carried out in the following ways. 1) Observation, 2) Interview, 3) Questionnaire, 4) Literature study, and 5) Documentation study. Data Analysis Techniques in this study using descriptive analysis. Based on the results of the research that has been described, it can be concluded that the perception of students of class XI F.8 towards learning cultural arts (music) SMAN 1 Suliki District is good. A good student perception of learning will allow students to understand the subject matter and achieve their learning abilities and goals. The better the student's perception of learning, the better the student's understanding of the subject matter so that the competence achieved will also be good.